An Empirical Assessment of Public Servants' Integrity in the Public Sector of Macao - Wong, Hio Nam (2025)
This study provides an empirical assessment of public servants’ integrity in Macao’s public sector, exploring how integrity is perceived, practiced, and promoted amid Macao’s unique administrative and socio-cultural context. Drawing on in-depth, semi-structured interviews with ten public servants from diverse departments and hierarchical levels, the research adopts a qualitative approach guided by the Theory of Public Service Motivation (PSM). The findings reveal that integrity fundamentally prioritizes public interest above personal gain, grounded in honesty, self-discipline, and ethical commitment. While organizational missions and formal codes offer guidance, individual values, professional ethics, and personal motivation are central to upholding integrity. Key enablers include mission-driven values, ethical leadership, supportive organizational culture, non-monetary incentives, and recognition. However, integrity is undermined by inconsistent ethics training, weak supervision, ineffective reporting mechanisms, and cultural factors such as close social networks and fear of retaliation. The effectiveness of mechanisms, such as internal regulations, anti-corruption agencies, and ethics training, varies across departments, often hindered by procedural gaps and societal norms. The study concludes that sustaining integrity in Macao’s public sector requires strengthening ethics education, enhancing leadership and culture, improving internal systems, and addressing systemic and societal risks. Limitations include the small, non-generalizable sample and focus on qualitative insights. Recommendations are targeted at policymakers, the supervisory institution, the Commission Against Corruption (CCAC), and institutional leaders for future reforms.